Taxonomic review of the genus Aldrichiopa Guimarães, 1971 (Diptera: Tachinidae) with notes on antennal morphology and description of a new species - Torres-Domínguez, Diana Marcela; Gallardo, Fabiana; Mulieri, Pablo R. (Zootaxa, 2024)
A redescription of the genus Aldrichiopa Aldrich, 1934 (Diptera: Tachinidae) is provided and a new species, Aldrichiopa serrata Torres-Domínguez & Mulieri sp. nov. is described from specimens collected in Argentina and Chile. A detailed morphological description of the egg, first instar larva, and adult male and female including terminalia are presented for the first time. Exhaustive photographic records, scanning electron microscopy images, morphological detail of antennal ultrastructure, and updated geographic distributions are provided for the two species of the genus, Aldrichiopa coracella (Aldrich) and A. serrata sp. nov. An identification key based on males is provided. The taxonomic placement of Aldrichiopa to subfamily and tribe is discussed and information on the hosts of this genus of small tachinid flies is compiled.